Wireless energy harvesting for mobile devices - Lu, Jian (2014)
Wireless energy harvesting is the technique to gather the ambient RF energy transmitted from a wireless router, radio broadcast, or TV broadcast to power up a sensor network without any interconnecting wires. In this project, a low RF power harvester design is presented to harvest the ambient energy in order to power a tag circuit. A matching circuit is designed to implement maximum power harvesting from the antenna. The operation of tag circuit is divided into two modes: active mode and standby mode. The tag circuit only requires 5uA at 2.5v in standby mode; excess energy will be stored in a buffer capacitor for accumulation until full operation mode. The system operates in the 2.4 GHz band require a minimum input RF power of -5dbm.